Generations of Women Historians Within and Beyond the Academy (Springer International Publishing, 2018)
This collection focuses on generations of early women historians, seeking to identify the intellectual milieu and professional realities that framed their lives. It moves beyond treating them as simply individuals and looks to the social and intellectual forces that encouraged them to study history and, at the same time, would often limit the reach and define the nature of their study. This collection of essays speaks to female practitioners of history over the past four centuries that published original histories, some within a university setting and some outside. By analysing the values these early women scholars faced, readers can understand the broader social values that led women historians to exist as a unit apart from the career path of their male colleagues.